2015
DOI: 10.1038/srep18612
|View full text |Cite
|
Sign up to set email alerts
|

The temporal topography of the N-Methyl- N-nitrosourea induced photoreceptor degeneration in mouse retina

Abstract: Retinitis pigmentosa (RP) is a group of inherited neurodegenerative diseases characterized by the progressive photoreceptors apoptosis. The N-Methyl- N-nitrosourea (MNU) is an alkylating toxicant which could induce photoreceptor apoptosis resembling that of the hereditary RP. However, the detailed process pattern of this degeneration remains poorly characterized. We systemically explored the topography of the photoreceptor degeneration in the MNU treated mouse, and related these spatial data with the time-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 44 publications
3
35
0
Order By: Relevance
“…Without the supports of topographic technologies, the effectively preserved zone might be readily overlooked, resulting in an underestimated therapeutic effect, or in contrast, a regional effect might be mistaken for global efficiency, giving rise to positive errors. 29 In the present study, TES-induced effects on the regional retina were systemically measured using topographic methods. Both the MEA and morphologic measurement suggested that the photoreceptors in the central retina were more efficiently preserved compared to the peripheral and midperipheral regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without the supports of topographic technologies, the effectively preserved zone might be readily overlooked, resulting in an underestimated therapeutic effect, or in contrast, a regional effect might be mistaken for global efficiency, giving rise to positive errors. 29 In the present study, TES-induced effects on the regional retina were systemically measured using topographic methods. Both the MEA and morphologic measurement suggested that the photoreceptors in the central retina were more efficiently preserved compared to the peripheral and midperipheral regions.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroretinal whole mounts were prepared according to previously described methods and were then divided into quadrant patches with four incisions, at 3, 6, 9, and 12 o'clock. 29 Total RNA was extracted from the pooled retinal patches with a commercial reagent (Trizol; Gibco, Inc., Grand Island, NY, USA), followed by cDNA synthesis using the lMACS DNA Synthesis kit (Miltenyi Biotech GmbH, Bergisch-Gladbach, Germany). Primer sequences are depicted in Table 1, and all primers were quality controlled by sequencing the template on a genetic ABI analyzer (Applied Biosystems, Inc., Foster City, CA, USA).…”
Section: Quantitative Reverse Transcription-polymerase Chain Reactionmentioning
confidence: 99%
“…The design of the treatment protocol was based on the basic pathological feature of animal model and previous pharmacological studies. Typically, the retinal degenerative process in MNU administered mice occurred within 7 days with a dose of 60 mg/kg [21,22]. This administered dose was considered as the optimum dose for model construction and has been used in multiple therapeutic trials [22,23].…”
Section: Methodsmentioning
confidence: 99%
“…Typically, the retinal degenerative process in MNU administered mice occurred within 7 days with a dose of 60 mg/kg [21,22]. This administered dose was considered as the optimum dose for model construction and has been used in multiple therapeutic trials [22,23]. MNU solution (5 mg/ml) was prepared by dissolving reagent in physiological saline containing 0.05% acetic acid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation